A Randomized Trial of Lymphadenectomy in Patients with Advanced Ovarian Neoplasms - Harter, Philipp; Sehouli, Jalid; Lorusso, Domenica; Reuss, Alexander; Vergote, Ignace; Marth, Christian; Kim, Jae-Weon; Raspagliesi, Francesco; Lampe, Björn; Aletti, Giovanni; Meier, Werner; Cibula, David; et al. (The New England journal of medicine, 2019)
BACKGROUND: Systematic pelvic and paraaortic lymphadenectomy has been widely used in the surgical treatment of patients with advanced ovarian cancer, although supporting evidence from randomized clinical trials has been limited. METHODS: We intraoperatively randomly assigned patients with newly diagnosed advanced ovarian cancer (International Federation of Gynecology and Obstetrics stage IIB through IV) who had undergone macroscopically complete resection and had normal lymph nodes both before and during surgery to either undergo or not undergo lymphadenectomy. All centers had to qualify with regard to surgical skills before participation in the trial. The primary end point was overall survival. RESULTS: A total of 647 patients underwent randomization from December 2008 through January 2012, were assigned to undergo lymphadenectomy (323 patients) or not undergo lymphadenectomy (324), and were included in the analysis. Among patients who underwent lymphadenectomy, the median number of removed nodes was 57 (35 pelvic and 22 paraaortic nodes). The median overall survival was 69.2 months in the no-lymphadenectomy group and 65.5 months in the lymphadenectomy group (hazard ratio for death in the lymphadenectomy group, 1.06; 95% confidence interval [CI], 0.83 to 1.34; P = 0.65), and median progression-free survival was 25.5 months in both groups (hazard ratio for progression or death in the lymphadenectomy group, 1.11; 95% CI, 0.92 to 1.34; P = 0.29). Serious postoperative complications occurred more frequently in the lymphadenectomy group (e.g., incidence of repeat laparotomy, 12.4% vs. 6.5% [P = 0.01]; mortality within 60 days after surgery, 3.1% vs. 0.9% [P = 0.049]). CONCLUSIONS: Systematic pelvic and paraaortic lymphadenectomy in patients with advanced ovarian cancer who had undergone intraabdominal macroscopically complete resection and had normal lymph nodes both before and during surgery was not associated with longer overall or progression-free survival than no lymphadenectomy and was associated with a higher incidence of postoperative complications. (Funded by Deutsche Forschungsgemeinschaft and the Austrian Science Fund; LION ClinicalTrials.gov number, NCT00712218.).
Keywords: dospělí; Kaplan-Meier Estimate; nádory vaječníků; lymfadenektomie; CA-125 Antigen; Female; Operative Time; Lymphatic Metastasis; lymfatické metastázy; Adult; mladý dospělý; ženské pohlaví; Kaplanův-Meierův odhad; doba přežití bez progrese choroby; lidé; Lymph Node Excision; Ovarian Neoplasms; pooperační komplikace; Aged, 80 and over; Treatment Failure; míra přežití; proporcionální rizikové modely; Postoperative Complications; Aged; antigen CA-125; Proportional Hazards Models; Young Adult; neúspěšná terapie; Survival Rate; délka operace; lidé středního věku; senioři nad 80 let; senioři; Progression-Free Survival; Middle Aged; Humans